Internalizing Prophetic Leadership Values: A Hadith-Based Framework for Youth Character Development - Mutiara Hasanah Nindi Puller (Young Journal of Social Sciences and Humanities, 2026)
In the digital age, the younger generation often faces many significant challenges, one of which is freedom of expression, particularly when voicing opinions. However, this freedom of expression is often not accompanied by ethical and moral responsibility. This has become a critical issue that requires proactive solutions to address it. This study aimed to revive the leadership values contained in the hadith of the Prophet Muhammad SAW and to develop a strategic framework for internalizing these values into the democratic character of today’s youth. This study employed a library research method with a qualitative-descriptive approach. Data were obtained from hadith collections (Kutubut Tis’ah) and contemporary scholarly literature on character education and democracy. This study found that hadiths on leadership contain key principles of democratic character, namely amanah (high integrity), justice, consultation, and responsibility (mas’uliyyah). The strategy for this internalization is formulated through a conceptual approach that integrates theological-moral awareness based on prophetic texts (the internalization of values), communication ethics through digital media discourse and the principle of tabayyun, as well as democratic values through dialogical reasoning and intellectual openness (syura).